EFEKTIVITAS DIRECT METHOD DALAM PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS MAHASISWA - fasaaro hulu; Ambalegin Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2018)
The purpose of this research is to find out how the ability of students to speak English before and after the experiment of the direct method and whether the students’ speaking ability improve by approaching the direct method directly through mastering grammar, vocabulary and pronunciation by, (Villalobos, 2010). And the experimental research model used is one group of pre-test and post-test experimental design (Cohen, Manion & Morrison, 2007), experimental (O1 X O2) Methods of data collection are consist of observation, interview and recording. Data analysis through grouping and comparison by category; unsatisfied category (US), fair category (F), good category (G), very good category (V) and excellent category (E). The results of the research base on the pre-test were included in the US category = 10 students, F = 26 students, G = 15 students, VG = 2 students and E = 0, no result found and post-test student learning outcomes US = 0, no result found, F = 7 students, G = 22 students, VG = 20 students and E = 4 students. Then the positive effect of using the direct method results is the students' ability in speaking English increased higher, refers to the pre-test results the student ability category found in US categories and no found the same category in the post-test results, the students ability category no result found in category E and the US category.